The Role of Health Literacy in The Prevention of Covid-19 - Rahman Panahi; Leila Dehghankar; Mohammad Anbari (Mashhad University of Medical Sciences, 2021)
The Covid-19 infectious disease is caused by a new coronavirus. Its outbreak was first discovered in Wuhan, China in December 2019, and it quickly became a pandemic of this century [1]. The rapid spread of the virus has caused countries to face a large number of infected people, so that as of August 8, 2020, globally, 19,187,943 people have been infected by the virus, and 716,075 people have died.. It is estimated that the mortality rate of this disease is between 1 to 5%, but it varies with age and other health conditions such as a history of underlying diseases . A significant proportion of deaths from Covid-19 infectious occur in the elderly and those with underlying diseases .Preventive behaviors play an important role in reducing the morbidity and mortality of this disease . Measures such as training, awareness promoting, attitude, and adopting preventative and protective actions are an important strategy to prevent Covid-19.